Low‐Temperature‐Processed WOx as Electron Transfer Layer for Planar Perovskite Solar Cells Exceeding 20% Efficiency. Issue 4 (31st January 2020) - Chen, Cong; Jiang, Yue; Wu, Yehui; Guo, Jiali; Kong, Xiangyu; Wu, Xiayan; Li, Yuzhu; Zheng, Dongfeng; Wu, Sujuan; Gao, Xingsen; Hou, Zhipeng; Zhou, Guofu; et al.
Abstract : Low‐temperature, solution‐processed metal oxides are of great interest as alternative materials for electron transport layers in perovskite solar cells. WO x is a promising candidate that could truly enable low‐temperature (<100 °C) processing. However, its amorphous‐state form typically obtained with the solution process suffers from high defect density. This causes large charge recombination, and consequently significant deterioration of the solar cell efficiency. Herein, an ultra‐low‐temperature processed (50 °C) nanocrystalline WO x as the electron transport layer, free of this problem, is demonstrated. This material is obtained by the reaction of tungsten chloride with hexanol, which induces transformation of the precursor solution into stable colloidal particles. The best solar cell, with the WO x electron transport layer, achieved an efficiency of 20.77%, which is a record performance for this class of perovskite solar cells. Abstract : Herein, a planar n–i–p perovskite solar cell based on a nanocrystalline WO x electron transfer layer is developed, with a low‐temperature fabrication process (50 °C) and record high efficiency, exceeding 20%.